Traffic Performance Analysis Since the Flyover is Construced (Jl. Indra Bangsawan) - Priawan, Ragil; sulistyorini, rahayu; karami, muhammad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
The increase in the number of vehicles is not in line with the increase in transportation infrastructure. The construction of flyovers is one of the measures to provide transportation infrastructure that helps to enhance thehighway capacity. However, there are several things that need to be considered of the construction of flyover. In addition to reducing traffic density, it is also necessary to pay attention to the new routes that will be chosen to be the solution to the existing traffic congestion. The research objective is to analyze the performance of the section of Jl. Indra Bangsawan in its existing condition and provides alternative solutions so that  it is more optimal. 1997 Indonesian Road Capacity is used to analyze the performance of this intersection.Based on the results of research, it is known that the existing conditions of each segment are saturated (DS> 0.70), namely in the first segment of 1.16, Segment II of 1.37 and Segment III of 1.24, with the highest density in segment II. To improve the performance of the section, several alternative improvements were made with widening road dimensions, applying one-way systems, closing lanes and controlling side barriers. From these alternatives an effective repair solution is the application of a one-way system and control of side barriers.Keywords: Degree of Saturation, Capacity, Density, Roads